2006
DOI: 10.1016/j.cep.2006.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic, thermal and ozone pre-treatments on waste activated sludge solubilisation and anaerobic biodegradability

Abstract: In order to enhance the efficiency of anaerobic digestion, the effects of ultrasounds, ozonation and thermal pre-treatment have been studied on waste activated sludge. The feature of this study was to carry out the comparison of the three pre-treatments in the same conditions and on the same sludge sample. Each treatment was tested in two conditions close to optimum conditions to maximise batch anaerobic sludge biodegradability. All treatments led to chemical oxygen demand and matter solubilisation and had lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
255
5
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 536 publications
(291 citation statements)
references
References 28 publications
28
255
5
3
Order By: Relevance
“…If it was continued with an anaerobic fermentation, the biogas amount increased significantly compared with the control. This finding was also agree well with the result of Bougrier et al (2006). Therefore, the pretreatment to textile mill biosludges, either ozonation or sonication, increased biochemical methane potential, then there would be a reduction in the biosludge residue.…”
Section: Effect Of Pretreatment Towards Biochemical Methane Potentialsupporting
confidence: 82%
See 4 more Smart Citations
“…If it was continued with an anaerobic fermentation, the biogas amount increased significantly compared with the control. This finding was also agree well with the result of Bougrier et al (2006). Therefore, the pretreatment to textile mill biosludges, either ozonation or sonication, increased biochemical methane potential, then there would be a reduction in the biosludge residue.…”
Section: Effect Of Pretreatment Towards Biochemical Methane Potentialsupporting
confidence: 82%
“…The increase of biodegradability with increasing ozone dosage was in accordance with the finding of Goel et al (2003) and Bougrier et al (2006). They found that CH 4 formation increased with increasing ozone dosage.…”
Section: Effect Of Pretreatment Towards Biochemical Methane Potentialsupporting
confidence: 78%
See 3 more Smart Citations